ANALYSIS OF THE DROWNED PEOPLE ON THE TERRITORY OF THE SLOVAK REPUBLIC IN YEARS 1991-2000 AND 2001-2010 (Fiep Bulletin - online, 2014)
The paper deals with the issue of risk level of the water environment in focus on the number of drowned people in Slovakia in years 1991-2010, statistically evaluates and analyzes the number of drowning victims in 10 years periods in terms of the nature of the water surface and the most common causes of drowning and age and specifies the major causes of drowning. In scientific work was used the method of content analysis of official injuries protocols in the water environment in the reporting period 1991-2010, the method of mathematical statistics, interview method in rescue participants and questionnaire to members of the Fire rescue service, Police Force and Water Rescue services. The authors have used the information provided through electronic media data (www). Based on the present analysis, the statement can be said that the statistics of the number of people drowned in the area of Slovak Republic reported high numbers every year. In order to reduce these numbers to the minimum, it is necessary to perform a lot of work especially in the field of prevention and awareness among the general population as well as in the training of water rescue members. It will be strictly necessary to finalize the main area of legislation which must be harmonized with EU legislation. The fulfilment of this process will require the involvement of a wide range of professional and volunteer staff of Water Rescue Service as well as other institutions (Parliament of Slovak Republic, schools, foundations, city and municipal councils), which are involved in physical activities of the population in area of water environment.
Keywords: drowning; water rescue; recreational activities; floods; swimming